INVESTMENT TRAINING MODERATES THE EFFECT OF FINANCIAL LITERACY, RETURN AND RISK ON INVESTMENT INTEREST IN CAPITAL MARKETS - Fadli, Anhar; Wijayanto, Andhi (Management Analysis Journal, 2020)
This study aims to analyze the effect of financial literacy, return and risk on investment interests in the capital market members of Forum KSPM Kota Semarang with investment research as a moderating variable. This research uses structural equation model analysis with WarpPLS 6.0 to evaluate the relationship between variables and the effect of moderation on investor investment training with financial literacy, return, risk, and investment interest by conducting a survey of 113 respondents who were successfully collected. The results of this study confirm previous findings that financial literacy has a positive effect on investment interest, returns have a positive effect on investment interest, and risk has a positive effect on investment interest. Researchers also found that investment training could not moderate the effect of financial literacy on investment interest, but investment training could moderate the effect of return and risk on investment training.